2019
DOI: 10.3390/ijms20123094
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as a Source and a Target for Uremic Toxins

Abstract: Elucidation of molecular and cellular mechanisms of the uremic syndrome is a very challenging task. More than 130 substances are now considered to be “uremic toxins” and represent a very diverse group of molecules. The toxicity of these molecules affects many cellular processes, and expectably, some of them are able to disrupt mitochondrial functioning. However, mitochondria can be the source of uremic toxins as well, as the mitochondrion can be the site of complete synthesis of the toxin, whereas in some scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 130 publications
2
36
0
Order By: Relevance
“…The uremic serum-induced increase in oxidative stress appears mainly mitochondria-derived and leads to NO scavenging. This is in line with other studies showing mitochondria as a source of oxidative stress upon uremic serum exposure, 45,46 which can lead to an increase in intracellular ROS and a reduction in NO level. 46,47 Superoxide is highly reactive and can rapidly react with NO to form peroxynitrite, which can cause damage, including nitration modification of the tyrosine residues of proteins, yielding 3NT, commonly used as a footprint of peroxynitrite formation.…”
Section: Discussionsupporting
confidence: 93%
“…The uremic serum-induced increase in oxidative stress appears mainly mitochondria-derived and leads to NO scavenging. This is in line with other studies showing mitochondria as a source of oxidative stress upon uremic serum exposure, 45,46 which can lead to an increase in intracellular ROS and a reduction in NO level. 46,47 Superoxide is highly reactive and can rapidly react with NO to form peroxynitrite, which can cause damage, including nitration modification of the tyrosine residues of proteins, yielding 3NT, commonly used as a footprint of peroxynitrite formation.…”
Section: Discussionsupporting
confidence: 93%
“…Creatinine is a product of degradation of creatine phosphate [82], one of the main energy substrates in mitochondria [83]. Therefore, the correlation between the levels of these metabolites might reflect the involvement of mitochondria in metabolic changes after AKI, which was previously indicated for a number of uremic toxins [84].…”
Section: Discussionmentioning
confidence: 93%
“…In this metabolic process urea and other amino groups are synthesised from the breakdown of the amino acids. Thus, the low concentration of urine hippurate observed in TB patients might be due to/connected to the synthesis of aromatic amino acids such as tryptophan, tyrosine and phenylalanine 39 , 40 . Alternatively , Weiner et al suggested that low serum hippurate concentrations might be related to uremic cytotoxic activity related to vitamin D metabolism 24 .…”
Section: Discussionmentioning
confidence: 99%